2009
DOI: 10.1007/s11626-009-9227-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of protocol for the isolation of Wharton’s Jelly stem cells in large-scale applications

Abstract: The Wharton's Jelly (WJ) of the umbilical cord (UC) is an excellent source of mesenchymal stem cells (MSCs) with a range of potential therapeutic applications. The present study was conducted to demonstrate the efficiency of the protocols used by Biogenea-Cellgenea Ltd. for isolation and expansion of WJ MSCs from donors across Greece. Umbilical cord samples were collected from 599 females following childbirth and processed for WJ MSC isolation. Stem cells were expanded using DMEM-based media and cell counts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 12 publications
1
32
0
1
Order By: Relevance
“…On the contrary, the classical expansion protocols for BM-MSCs, accepted for clinical use by the regulatory agencies [4], still employ FBS with FGF-2 as the medium additional supplement, which provides excellent results [37,38]. However, with regard to the present study, it should be noted that no major changes were observed in the phenotype characteristics and properties of BM-MSCs expanded in the presence of PL or FBS [34,36,39].…”
Section: Discussionmentioning
confidence: 57%
“…On the contrary, the classical expansion protocols for BM-MSCs, accepted for clinical use by the regulatory agencies [4], still employ FBS with FGF-2 as the medium additional supplement, which provides excellent results [37,38]. However, with regard to the present study, it should be noted that no major changes were observed in the phenotype characteristics and properties of BM-MSCs expanded in the presence of PL or FBS [34,36,39].…”
Section: Discussionmentioning
confidence: 57%
“…Wharton's jelly-derived mesenchymal stem cells (WJ-MSC) were isolated, as reported elsewhere (24), from the umbilical cords obtained from the infants delivered by cesarean section while informed consent was obtained from their parents. The umbilical cord vein was flashed with PBS, the arteries were removed, and the rest were cut into small pieces.…”
Section: Wharton's Jelly-derived Mesenchymal Stem Cells Isolation Andmentioning
confidence: 99%
“…Recently, a new method has been proposed for the isolation of MSCs from Wharton's jelly by the direct delivery of enzymatic solutions into the tissue, similar to the method used for the enzymatic digestion of the pancreas for Langerhans islet isolation (50). To avoid the disadvantages of enzymatic digestion, which has been shown to potentially alter cell proliferation and function, some groups have developed UC explant culture approaches that have been shown to be simple, reproducible, and efficient (63)(64)(65)(66). However, considering the heterogeneity of the processes used for cell isolation and expansion, and in view of their use for clinical applications, some groups have tried to develop optimized and standardized methods based on the use of xeno-and serum-free culture media (52,67,68) or by taking advantage of the plastic-adherence properties of MSCs that allow cell expansion without UC dissection or enzymatic digestion (69).…”
Section: Isolation and Expansion Of Huc-mscsmentioning
confidence: 99%